1987
DOI: 10.1017/s0021859600064108
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of liquid manure (urine and water) and nitrogen fertilizers applied to a grass-clover sward on soils of different pH value

Abstract: SummaryIn a 3-year plot experiment on a perennial ryegrass plus white clover sward the pH of the soil on the main plots was adjusted to, and maintained as nearly as possible at, target levels of 5·25, 6·00 and 6·75 by applying either sulphur or lime. Within the main plots the effects on herbage yield, clover content and crude-protein content of applying four fertilizers were compared at nitrogen rates of 225 and 450 kg/ha annually. The fertilizers were liquid manure (urine plus water), prilled urea, a urea sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Grass yields were not different when inorganic or manure fertilizers were applied in both hayfields, suggesting that similar yields can be obtained when decomposition coefficients and N‐loss factors are used to match inputs of manure N to inorganic N fertilizer. Our results are consistent with yields reported in grasslands that received the same N input from manure and inorganic fertilizer even though the P and K loadings differed (Min et al, 1999a, 1999b; Estavillo et al, 1996; Castle and Reid, 1987). The manure‐fertilized plots increased the P and K concentrations slightly compared to unfertilized plots in the Bromus – Poa hayfield, but statistical differences were not found in the Pleum – Lolium hayfield.…”
Section: Discussionsupporting
confidence: 89%
“…Grass yields were not different when inorganic or manure fertilizers were applied in both hayfields, suggesting that similar yields can be obtained when decomposition coefficients and N‐loss factors are used to match inputs of manure N to inorganic N fertilizer. Our results are consistent with yields reported in grasslands that received the same N input from manure and inorganic fertilizer even though the P and K loadings differed (Min et al, 1999a, 1999b; Estavillo et al, 1996; Castle and Reid, 1987). The manure‐fertilized plots increased the P and K concentrations slightly compared to unfertilized plots in the Bromus – Poa hayfield, but statistical differences were not found in the Pleum – Lolium hayfield.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have shown less negative effect on the clover content by slurry than from an equivalent inorganic N fertilization (Dilz & Mulder, 1962;Castle & Reid, 1987;Chapman & Heath, 1987;Nesheim et al, 1990). The negative effect of inorganic N on clover may be offset by applying suf cient amounts of potassium (Chapman & Heath, 1987).…”
Section: H Steinshamnmentioning
confidence: 99%
“…Numerous studies have shown that N applied as slurry or manure can reduce the clover content of a sward (Drysdale 1966;Castle & Reid 1987;Chapman & Heath 1988;Nesheim et al 1990;Estavillo et al 1996). Barr (1996), however, noted that even under high N use as fertiliser (400 kg N ha" 1 yr" 1 ) clover could persist, provided the sward is not permitted to re-grow more than 1200 kg DM ha" 1 between grazings.…”
Section: Effect Of Management Systems On Pasture Compositionmentioning
confidence: 99%